Age-Dependent Effects of Butyl Benzyl Phthalate Exposure on Lipid Metabolism and Hepatic Fibrosis in Mice - Min-Seo Park; Seonhwa Hwang; Hyun-Bon Kang; Minjeong Ha; Juyeon Park; So-Youn Park; Yong-Joo Park; Min-Hi Park (Cells)
Endocrine-disrupting chemicals (EDCs), including phthalates, have been implicated in the development of non-alcoholic fatty liver disease (NAFLD) and hepatic fibrosis. This study investigates the age-dependent effects of butyl benzyl phthalate (BBP) exposure on lipid metabolism in the livers of young and aged mice. Young (2-month-old) and aged (20-month-old) male C57BL/6 mice were exposed to BBP through drinking water at a dose of 169 μg/kg/day for 6 and 4 months, respectively. Young mice exposed to BBP showed fatty liver, with downregulation of key fatty acid oxidation genes (CPT1A, CPT1B, CPT2, and Acox1) and elevated pro-inflammatory cytokines (TNF-α and IL-6). In contrast, aged mice exhibited hepatic fibrosis, with increased collagen deposition and upregulation of genes related to fibrosis (Acta2, MMP2, TGF-ß1, and Col1a2), cirrhosis (CXCR4, SOX9, DCN, and MFAP4), and cancer (Bcl2, CDKN2a, c-Myc, and Fn1). Overall, these findings emphasize the importance of age when evaluating the risks of EDC exposure, such as BBP. Future research should focus on understanding the molecular mechanisms behind these age-related differences and explore Grem1 and SOCS3 as potential therapeutic targets for treating EDC-induced and age-related liver diseases.